Reforming the insurance sector and its role in stimulation gross domestic product in Iraq for the period (2014-2018) - alabee, donya kadum; dawood, Sameer siham (Journal of Economics and Administrative Sciences, 2020)
The main purpose of the research is to demonstrate the importance of the insurance sector in the economy through its role in providing security for all economic sectors and thus stimulating the gross domestic product and reducing dependence on the output of the oil sector, which may expose the Iraqi economy to several problems and imbalances, I have found that there is a great weakness in the role of the insurance sector in Iraq at the level of government, companies and individuals, and the reason for this is the lack of policies supporting the insurance sector and the lack of work in the strategy of economic diversity and the decrease of security awareness by individuals so became Developing the sector to ensure the urgent need to keep pace with economic developments by working on the existence of special policies that support the insurance sector as part of the strategies of economic diversification and work to increase security awareness.